2005
DOI: 10.1103/physrevd.72.103518
|View full text |Cite
|
Sign up to set email alerts
|

Stability properties of some perfect fluid cosmological models

Abstract: Flat FRW perfect fluid cosmologies can be reproduced as particular solutions of suitable field theoretical models. Here we investigate the stability of perfect fluid model trajectories with respect to sets of trajectories of the corresponding field models having generic initial conditions. It is shown that the trajectories of barotropic perfect fluid models and those of the Chaplygin gas model are stable. The total probability to reach the Chaplygin gas regime early enough to achieve a matter dominated stage h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 58 publications
1
88
0
Order By: Relevance
“…Assuming that the kinetic term is of Born-Infeld type, as in Refs. [43,44,47,48,49], 15) with M a suitable mass-scale, which implies ρ = f (ϕ)/ 1 − 2X/M 4 , we get…”
Section: A Lagrangians Of the Typementioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the kinetic term is of Born-Infeld type, as in Refs. [43,44,47,48,49], 15) with M a suitable mass-scale, which implies ρ = f (ϕ)/ 1 − 2X/M 4 , we get…”
Section: A Lagrangians Of the Typementioning
confidence: 99%
“…If one requires the exact condition that our unified DM fluid has a constant pressure term p = −Λ and looks for a scalar field model with canonical kinetic term, one arrives at an exact solution with potential V (φ) = (Λ/2)[cosh 2 ( √ 3φ/2) + 1] (see also Ref. [43,44]). Using standard criteria (e.g.…”
Section: Unified Dark Matter From a Scalar Field With Non-canonicmentioning
confidence: 99%
“…This issue has already been investigated for some DE models. It was shown that chaplygin gas and tachyon DE have positive squared speeds of sound with, v 2 s = −w, and thus they are supposed to be stable against small perturbations [29,30]. However, the perfect fluid of holographic DE with future event horizon is classically unstable because its squared speed is always negative [31] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for the background solutions these two ways to describe dark energy models are equivalent. However, one cannot assume univocally this equivalence, for example in the stability of the solutions [31] or in the studies of cosmological perturbations [13,32].…”
Section: Introductionmentioning
confidence: 99%